2020
DOI: 10.1111/jipb.12892
|View full text |Cite
|
Sign up to set email alerts
|

New insights into gibberellin signaling in regulating flowering in Arabidopsis

Abstract: In angiosperms, floral transition is a key developmental transition from the vegetative to reproductive growth, and requires precise regulation to maximize the reproductive success. A complex regulatory network governs this transition through integrating flowering pathways in response to multiple exogenous and endogenous cues. Phytohormones are essential for proper plant developmental regulation and have been extensively studied for their involvement in the floral transition. Among various phytohormones, gibbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
170
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(176 citation statements)
references
References 136 publications
(186 reference statements)
3
170
0
3
Order By: Relevance
“…The floral transition is a critical developmental phase for reproductive success and is tightly controlled by a complex genetic network in response to various environmental and developmental signals (Andres and Coupland 2012;Song et al 2013;Bao et al 2020). The flowering signals from these multiple genetic pathways ultimately converge on the regulation of floral pathway integrators, FLOWERING LOCUS T (FT), SUP-PRESSOR OF OVEREXPRESSION OF CONSTANS1 (SOC1), and LEAFY (LFY; Kardailsky et al 1999;Blazquez and Weigel 2000), which in turn activate downstream floral meristem identity genes, including LFY and APETALA1 (AP1), to initiate the generation of floral meristems (Blazquez and Weigel 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The floral transition is a critical developmental phase for reproductive success and is tightly controlled by a complex genetic network in response to various environmental and developmental signals (Andres and Coupland 2012;Song et al 2013;Bao et al 2020). The flowering signals from these multiple genetic pathways ultimately converge on the regulation of floral pathway integrators, FLOWERING LOCUS T (FT), SUP-PRESSOR OF OVEREXPRESSION OF CONSTANS1 (SOC1), and LEAFY (LFY; Kardailsky et al 1999;Blazquez and Weigel 2000), which in turn activate downstream floral meristem identity genes, including LFY and APETALA1 (AP1), to initiate the generation of floral meristems (Blazquez and Weigel 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Gibberellin signalling in Arabidopsis is regulated via its ability to mediate the degradation of DELLA proteins, a family of growth inhibitors. The degradation of DELLAs de-represses the DELLA interacting proteins which in turn positively regulate growth (Bao et al 2020; Davière and Achard, 2016). Most of the available literature on DELLAs is based on work in the L er -background.…”
Section: Resultsmentioning
confidence: 99%
“…According to the above functional classi cations and WGCNA of these DEGs, and owering-related genes previously reported in model plants (such as A. thaliana) [5,7], a total of 146 unigenes were identi ed as homologous genes related to oral transition in L. gratissima, involving several owering pathways: sugar metabolism, hormone metabolism and signal transduction, photoperiod, ambient temperature, aging pathways, as well as oral integrator and oral meristem identity genes. Among these oral transition-related homologous genes, stage-speci c DEGs, and common DEGs in LD7-vs.-SD7, LD10-vs.-SD10, LD13-vs.-SD13, and LD19-vs.-SD19 are listed in Additional le 13: Table S7.…”
Section: Identi Cation Of Deg Expression Patterns Associated With Oramentioning
confidence: 99%
“…Many studies have demonstrated that various phytohormones participate in the regulation of oral transition [7,[14][15][16]. A total of 20 (13.70%) DEGs associated with phytohormone metabolism were identi ed, and these involved 16 phytohormone metabolism homologous genes and were related to nine phytohormone metabolism pathways.…”
Section: The Expression Patterns Of Phytohormone Metabolism and Signamentioning
confidence: 99%
See 1 more Smart Citation